Extraneural metastases in ependymoma of the cauda equina - Rubinstein, Lucien J. (1970)
A case of ependymoma of the cauda equina, presumably originating from the filum terminale in a girl aged 17 at the onset of illness, eventually developed remote metastases in the lungs, pleura, and one para-aortic lymph node. This case is compared with three other previously reported examples. The unusual features in the present instance were (1) the total length of the clinical history, amounting to 29 years; (2) the development, six years after the removal of the original spinal tumour, of another ependymomatous mass in the fourth ventricle, interpreted as a rostral metastasis that seeded via the cerebrospinal fluid; and (3) the demonstration of anaplastic cytological changes at the primary site, interpreted as the result of irradiation. The salient aspects of this and the three other reported cases are briefly reviewed, and the pathway of distant dissemination, resulting from venous permeation at the primary site, is emphasized.